Literature Review: Manfaat Tradisional, Kandungan Fitokimia, Aktivitas Farmakologis, dan Potensi Pengembangan Sediaan Antibakteri dari Tumbuhan Kakao (Theobroma cacao L.) - Agaphe Suluh Brahmantio; Ramadhan Triyandi; Zulpakor Oktoba; Femmy Andrifianie; Muhammad Iqbal (STIKES Columbia Asia Medan, 2025)
The cacao plant (Theobroma cacao L.) has long been used in traditional medicine and has been proven to contain phytochemical compounds such as polyphenols, flavonoids, alkaloids, and tannins, which exhibit pharmacological activities, including antioxidant, anti-inflammatory, and antibacterial properties. This study aims to review the potential development of antibacterial formulations based on cacao extract through a literature review. The method used is a qualitative descriptive analysis of national and international journals published in the last 10 years. The review results indicate that extracts from cacao seeds, fruit peels, and leaves are effective in inhibiting the growth of various pathogenic bacteria, both Gram-positive and Gram-negative. Various formulations such as gels, creams, lotions, soaps, toothpaste, and mouthwash have been developed with promising results. The utilization of the cacao plant as an antibacterial agent in pharmaceutical formulations holds great potential as a natural alternative in the healthcare field while also adding value to cocoa industry by-products.